The midwifery in West Pomerania in the years of 1945–1948 - Kozłowska, Urszula; Bulsa, Marek (Nursing Problems / Problemy Pielęgniarstwa, 2012)
The results of war affect the society, individuals in direct and indirect ways. People become more susceptible to different kinds of illnesses, their life conditions deteriorate and, thus their of health decreases. The lack of suitable medical infrastructure, medical personnel who might meet the basic medical needs of the people are the main reasons. The aim of the paper is the presentation of selected problems connected with midwifery development in West Pomerania in the pioneer years of 1945–1948. This time was very specific for this area. It was characterized by special dynamic of social life, the manifestation of which was the creation of a new sociopolitical order. This was also the time of struggling with different social processes, often of dynamic character. Special attention was paid to issues connected with professional staff, especially the severe shortage of midwives after the second world war, and also on the development of institutions providing preventive and medical services for to pregnant women.